Analisis Hukum Ekonomi Kewajiban Sertifikasi Halal Terhadap UMKM Perspektif Maqashid Syariah - Nana Khoirina Daulay; Zulham (JOM, 2025)
This study focuses on the analysis of Sharia economic law in Percut Sei Tuan District, where many vendors sell food products without halal certification. The inclusion of a halal label is crucial to protecting Muslim consumers, considering the religious obligation to consume halal food. Food is a basic necessity widely consumed in society, and ensuring its halal status provides a sense of safety and comfort for consumers. This research aims to analyze the obligation of halal certification for Micro, Small, and Medium Enterprises (MSMEs) in the area and its implications for consumer protection. The method used is empirical juridical, with primary data collected through interviews and secondary data from literature studies. The findings reveal that despite the obligation to obtain halal certification, none of the 10 MSME samples studied had such certification. This indicates a gap between regulations and their implementation in the field. Therefore, halal certification is essential not only for legal compliance but also to assure Muslim consumers that the products they consume are free from unlawful substances. Halal certification is based on the principles of Maqashid Shariah, which aim to safeguard societal welfare and prevent fraud, in line with Islamic principles. This study emphasizes the need for further efforts to enhance awareness and compliance among MSMEs regarding halal certification for the health and safety of consumers.